2021
DOI: 10.4168/aair.2021.13.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Total IgE as a Marker for Chronic Spontaneous Urticaria

Abstract: Objective: Immunoglobulin E (IgE) and its receptor, FcɛRI, importantly contribute to the pathophysiology of chronic spontaneous urticaria (CSU). Recent findings point to a possible role of total IgE as a marker of CSU disease activity, endotypes, and responses to treatment. The evidence in support of total IgE included in the diagnostic workup of patients with CSU has not yet been reviewed. Methods: Publications were searched via PubMed. The search terms used were "chronic urticaria" and "total IgE." Studies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 73 publications
3
66
2
5
Order By: Relevance
“…In all adult CSU patients, we strongly recommend a) checking for symptoms of autoimmune diseases and screening for IgG anti-TPO with annual reassessment of thyroid function in positive asymptomatic cases; and b) a follow-up on a regular basis of patients with aiCSU, especially female patients with HT and/or a positive family history, to screen for signs and symptoms of other autoimmune diseases. 11 41 Further studies are needed and should use additional markers for aiCSU, for example total IgE 52 or the ratio of IgG anti-TPO to total IgE, a recently reported marker for aiCSU. 4 …”
Section: Discussionmentioning
confidence: 99%
“…In all adult CSU patients, we strongly recommend a) checking for symptoms of autoimmune diseases and screening for IgG anti-TPO with annual reassessment of thyroid function in positive asymptomatic cases; and b) a follow-up on a regular basis of patients with aiCSU, especially female patients with HT and/or a positive family history, to screen for signs and symptoms of other autoimmune diseases. 11 41 Further studies are needed and should use additional markers for aiCSU, for example total IgE 52 or the ratio of IgG anti-TPO to total IgE, a recently reported marker for aiCSU. 4 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that these phenotype-specific DMPs or DMGs will become potential biomarkers of the corresponding CSU subtypes. According to the study of Altrichter et al, low tIgE may suggest type IIb autoimmune CSU, poor response to treatment with omalizumab, and a better chance to benefit from cyclosporine treatment (37). The study of Kolkhir et al showed that 28% of CSU patients had at least one autoimmune disease and the most prevalent comorbid autoimmune disease was Hashimoto's thyroiditis (21%) (38).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of serum IgE were often found not only in atopic patients but also in chronic urticaria. Omalizumab is now regarded as the first-line drug for antihistamine-resistant chronic urticaria [14][15][16]. Omalizumab was found to be more effective for chronic urticaria patients with higher serum concentrations of IgE, whereas cyclosporine was efficacious for those with lower IgE [15].…”
Section: Roles Of Ige In Urticariamentioning
confidence: 99%
“…Omalizumab is now regarded as the first-line drug for antihistamine-resistant chronic urticaria [14][15][16]. Omalizumab was found to be more effective for chronic urticaria patients with higher serum concentrations of IgE, whereas cyclosporine was efficacious for those with lower IgE [15]. The pathological roles of IgE and FcεRI in chronic urticaria are classified into type I and type IIb; in the type I group, autoreactive IgEs, which could recognize autoantigens, such as thyroid peroxidase, tissue factor, thyroglobulin, double strand DNA, and IL-24, are produced [17][18][19][20], and in the type IIb group, IgM or IgG that could recognize IgE or FcεRI is produced.…”
Section: Roles Of Ige In Urticariamentioning
confidence: 99%